2013
DOI: 10.5539/gjhs.v6n1p33
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Behavioral Modification Based on Client Center Program to Health Behaviors among Obese University Students

Abstract: The objectives of this research were to examine the effectiveness of Health Behavioral Modification based on the Client Center Program (HBMCCP) and to study behavioral change in relation to self – efficacy, self- regulation, self-care behaviors and body weight. The sample was 59 undergraduate students, who were selected by cluster random sampling. 29 participated in the HBMCCP for 8 weeks, and were followed up 4 weeks after the program, and 30 students in the control group. Data was collected 3 times, before, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…After participating in the program, students in the experimental group reported significantly higher perceived self-efficacy in regulating their physical activity and dietary behaviors at all time points compared with students in the control group. These findings are consistent with those observed after a health promotion program for obese university students in Thailand in 2014 (Intarakamhang & Malarat, 2014) and an interventional study in Canada aimed at increasing university students' physical activity levels (Cotten & Prapavessis, 2016). Both our results and those of similar studies indicate that motivation and self-efficacy can effectively be increased using the methodology employed in the present study, which consisted of providing web-based education, setting weekly goals after the education sessions, allowing participants to listen to the session recordings again on the website, providing individual counseling, sending daily reminders through the WhatsApp smartphone application, and encouraging competition by rewarding successful students.…”
Section: Muntanersupporting
confidence: 91%
“…After participating in the program, students in the experimental group reported significantly higher perceived self-efficacy in regulating their physical activity and dietary behaviors at all time points compared with students in the control group. These findings are consistent with those observed after a health promotion program for obese university students in Thailand in 2014 (Intarakamhang & Malarat, 2014) and an interventional study in Canada aimed at increasing university students' physical activity levels (Cotten & Prapavessis, 2016). Both our results and those of similar studies indicate that motivation and self-efficacy can effectively be increased using the methodology employed in the present study, which consisted of providing web-based education, setting weekly goals after the education sessions, allowing participants to listen to the session recordings again on the website, providing individual counseling, sending daily reminders through the WhatsApp smartphone application, and encouraging competition by rewarding successful students.…”
Section: Muntanersupporting
confidence: 91%
“…The Effect of the Public Health Nursing Course Original Article university students have shown that students improve their healthy lifestyle behaviors, increase their physical activity (PA) levels, increase the consumption of vegetables and fruits, and the program causes weight loss and changes in body composition (10)(11)(12)(13)(14)(15). Moreover, there are subjects related to health behaviors in courses such as public health nursing and health promotion in nursing undergraduate education.…”
Section: Introductionmentioning
confidence: 99%